Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility